2022
DOI: 10.1039/d1ma00661d
|View full text |Cite
|
Sign up to set email alerts
|

High-k dielectric screen-printed inks for mechanical energy harvesting devices

Abstract: There are a range of promising applications for devices that can convert mechanical energy from their local environment into useful electrical energy. Here, mechanical energy harvesting devices have been developed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…102,103 Secondly, it is necessary to maintain the mechanical stability between the IFE and the polymer matrix of the IFE-polymer nanocomposite. 104 The higher thickness of the IFE films (greater than 100 nm) causes mechanical instability between the IFE film and the polymer matrix, which creates delamination or a crack in the films. 105 This can be improved only by playing with the interfacial energy between the IFE and the polymer.…”
Section: Perspectives and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…102,103 Secondly, it is necessary to maintain the mechanical stability between the IFE and the polymer matrix of the IFE-polymer nanocomposite. 104 The higher thickness of the IFE films (greater than 100 nm) causes mechanical instability between the IFE film and the polymer matrix, which creates delamination or a crack in the films. 105 This can be improved only by playing with the interfacial energy between the IFE and the polymer.…”
Section: Perspectives and Concluding Remarksmentioning
confidence: 99%
“…105 One possible method has been to functionalize the IFE surface with a low interfacial energy polymer matrix. 104,106,107 This in turn eliminates the defects associated with agglomeration and elevates the dispersibility. 104 Thus, the formation of nanoceramic-polymer composites has become a popular method for transforming an IFE bulk dielectric ceramic into the printable inks required for high productivity and industrial applications.…”
Section: Perspectives and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…88,[109][110][111][112][113][114][115][116][117] Hybrid structures consisting of ion gels, electrolytes, and high-k metal-oxideembedded polymer dielectrics showed improved dielectric constants and low voltage operation. [118][119][120][121] Recently, dielectric inks containing 2D h-BN have been developed to achieve excellent printability and high-k dielectrics. [122][123][124][125] Zhu et al reported a one-pot coating of a flexible pinhole-free polyurethane (PU)/ h-BN composite (Fig.…”
Section: Inks For Flexible Printed Electronic Devicesmentioning
confidence: 99%
“…Within this type of material, electroactive polymers and their composites allow their implementation as electro-mechanical systems (MEMS), enabling applications such as sensors and actuators, energy harvesting, and storage applications, among others . Electroactive materials allow customizable mechanical, thermal, and chemical properties and versatility with regard to processing techniques, including a variety of additive manufacturing, such as screen and inkjet printing. , …”
Section: Introductionmentioning
confidence: 99%